2020
DOI: 10.3390/polym12030680
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of Gel Carriers as Metronidazole Delivery Systems to the Oral Mucosa

Abstract: Periodontal diseases are some of the most widespread oral afflictions, and they are labeled as chronic infections caused by the accumulation of bacteria in dental plaque that produces localized inflammation of the periodontium. The use of local drug delivery systems to treat periodontal diseases has received greater attention, because the active substance is targeted directly to the affected area, which minimizes its systemic side effects. Therefore, the purpose of the investigation was to develop and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 45 publications
(42 reference statements)
2
32
0
Order By: Relevance
“…This feature was associated with the hydroxyl group contribution of the MTZ that increased the probability of H-bonding interactions between the skin tissue surface and the MTZ-containing hydrogels. Wróblewska et al [ 42 ] found that MTZ-containing gel formulations (bigels, hydrogels, oleogels) exhibit higher adhesive forces on porcine buccal mucosa than the formulations without MTZ.…”
Section: Resultsmentioning
confidence: 99%
“…This feature was associated with the hydroxyl group contribution of the MTZ that increased the probability of H-bonding interactions between the skin tissue surface and the MTZ-containing hydrogels. Wróblewska et al [ 42 ] found that MTZ-containing gel formulations (bigels, hydrogels, oleogels) exhibit higher adhesive forces on porcine buccal mucosa than the formulations without MTZ.…”
Section: Resultsmentioning
confidence: 99%
“…Bigels display the merits of both the aqueous and oil phase, including the ability to deliver simultaneously hydrophilic and lipophilic active agents, and improved viscoelasticity [ 26 ]. Bigels have been mainly applied in cosmetic/pharmaceutical formulations, since their hybrid characteristics are proven to maximize moisturizing benefits for the skin and simplify the penetration of active agents to deeper layers of the skin tissue [ 27 , 28 , 29 , 30 ]. These benefits may also be very valuable for food applications in the delivery of bioactive compounds [ 31 ].…”
Section: Hydrogels Oleogels Bigels and Emulgelsmentioning
confidence: 99%
“…The plates were subsequently incubated at 37.0 ± 0.1 • C either for 24 h (C. albicans, C. krusei) or 48 h (C. parapsilosis). After that time, the inhibition zones were measured [48]. For pure DMSO, no effect on the fungi proliferation was observed.…”
Section: Antifungal Activity Testmentioning
confidence: 99%
“…Considering the potential effect of the freezing process on the buccal mucosa integrity, we tried to minimize the effect of storage conditions on the measurement's variations according to the previous attempts performed by our research group [46,48]. For that purpose, the buccal mucosa was carefully selected in order to eliminate potential differentiations arising from inhomogeneity of the mucosal surface.…”
Section: Mucoadhesive Propertiesmentioning
confidence: 99%